2022
DOI: 10.1093/infdis/jiac192
|View full text |Cite
|
Sign up to set email alerts
|

Waning Immunity Against Respiratory Syncytial Virus During the Coronavirus Disease 2019 Pandemic

Abstract: Health jurisdictions have seen a near-disappearance of Respiratory Syncytial Virus (RSV) during the first year of the COVID-19 pandemic. Over a corresponding period, we report a reduction in RSV antibody levels and neutralization in women and infants one year into the COVID-19 pandemic (February – June 2021) compared to earlier in the pandemic (May – June 2020), in British Columbia (BC), Canada. This supports that humoral immunity against RSV is relatively short-lived and its establishment in infants requires … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
70
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(76 citation statements)
references
References 12 publications
6
70
0
Order By: Relevance
“…Susceptible children might be exposed for the first time at older ages (figure). Decreased maternal exposures and immunity to usual endemic viruses, 15 leading to a lack of transferred transplacental antibodies, might also leave young infants more vulnerable to viral infections. Age-related differences in disease presentations are likely to vary by pathogen.…”
Section: Preparing For Uncertainty: Endemic Paediatric Viral Illnesse...mentioning
confidence: 99%
“…Susceptible children might be exposed for the first time at older ages (figure). Decreased maternal exposures and immunity to usual endemic viruses, 15 leading to a lack of transferred transplacental antibodies, might also leave young infants more vulnerable to viral infections. Age-related differences in disease presentations are likely to vary by pathogen.…”
Section: Preparing For Uncertainty: Endemic Paediatric Viral Illnesse...mentioning
confidence: 99%
“…13,15,16 In this study, the changes in the positive rates and the seasonal patterns of HIFV, HRSV, and In addition, the changes in the positive rates and the seasonal patterns of respiratory viruses, which were caused by the implementation of NPIs, were likely to lead to a decline in herd immunity against them. Reicherz et al 39 have found that HRSV antibody levels and neutralization were reduced in women and infants 1 year into the COVID-19 pandemic compared to earlier in the pandemic. With the relaxation of NPIs and waned immunity in young children may lead to the resurgence of respiratory virus infection, and even lead to larger or more severe outbreaks, especially in children.…”
Section: Discussionmentioning
confidence: 99%
“…Infants are protected through transplacentally derived maternal antibody in the first several weeks of life. Low levels of RSV circulation will lead to waning population RSV antibody titres, and subsequently lead to lower levels of maternal antibody being transferred to infants during gestation 103 . This has the potential to result in a birth cohort with low levels of maternally derived antibody to experience their first RSV season, at a time when RSV circulation is much higher than in prior years.…”
Section: Health Care Burden Of Non-sars-cov-2 Virusesmentioning
confidence: 99%